2021
DOI: 10.1007/s00705-020-04846-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary vaccination in foals: a comparison of the serological response to equine influenza and equine herpesvirus vaccines administered concurrently or 2 weeks apart

Abstract: This study compared concurrent and separate primary vaccination against equid alphaherpesviruses 1 and 4, genus Varicellovirus, subfamily Alphaherpesvirinae, family Herpesviridae, and equine influenza A virus, genus Alphainfluenzavirus, family Orthomyxoviridae. Their vernacular names are equine herpesvirus 1 and 4 (EHV1/4) and equine influenza virus (EIV). Infection with these respiratory pathogens is associated with loss of performance, interruption of training schedules, and on occasion, cancellation of eque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…This result contradicts that of Gildea et al [ 12 ], in which horses immunized with EIV and EHV on the same day had significantly higher antibody levels 2 weeks post-vaccination than those immunized with EIV alone. In addition, our results also contradicted those of Allkofer et al [ 7 ], where the mean antibody titer of separately vaccinated horses was significantly higher than that of concurrently vaccinated horses at 2 weeks post-vaccination. These differences are probably attributable to the types of vaccines and adjuvants, influenza vaccine strains, and variations in horse species in the experiments.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This result contradicts that of Gildea et al [ 12 ], in which horses immunized with EIV and EHV on the same day had significantly higher antibody levels 2 weeks post-vaccination than those immunized with EIV alone. In addition, our results also contradicted those of Allkofer et al [ 7 ], where the mean antibody titer of separately vaccinated horses was significantly higher than that of concurrently vaccinated horses at 2 weeks post-vaccination. These differences are probably attributable to the types of vaccines and adjuvants, influenza vaccine strains, and variations in horse species in the experiments.…”
Section: Discussioncontrasting
confidence: 99%
“…EHV is an alpha-herpesvirus of the Herpesviridae family that induces symptoms of upper respiratory diseases similar to those induced by EI; however, it also causes abortion in mares and neurological disorders, such as EHV myeloencephalopathy, in foals [ 6 ]. These viruses spread quickly, especially in naïve populations, leading to the implementation of movement restrictions for horses and disruption of equestrian events [ 7 ]. Additionally, because of their high morbidity, infections with these viruses require strict prevention protocols including disease surveillance, quarantine of affected horses, and regular vaccination programs, which ultimately cause enormous financial losses in the equine industry [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A booster must be applied six months after the initial vaccination program. This booster provides protection for 12 months [ 96 , 97 ]. However, it has been reported that annual booster vaccination should not be relied on as the sole preventative measure against EIV, and increasing the frequency of booster vaccinations may be beneficial, particularly in young horses in places with high EIV transmission [ 88 ].…”
Section: Prevention and Controlmentioning
confidence: 99%
“…Influenza viruses are of international importance due to the widespread infection in different livestock, leading to vaccination being utilized across the veterinary field ( 2 ). Equine influenza viruses are important horse pathogens with policies in place that require horses be vaccinated for equine influenza viruses before participation in events or importation ( 3 , 4 ). Furthermore, due to the transmission of influenza viruses from horses to dogs, as well as the endemic infection of influenza viruses in the canine population, canine vaccination is also recommended for dogs with high risk of exposure ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%